Helicopter parenting and alcohol use in adolescence: A quadratic relation. Issue 2 (April 2022) - Pistella, Jessica; Isolani, Stefano; Morelli, Mara; Izzo, Flavia; Baiocco, Roberto
Aims: Research has underscored that an excessively intrusive parental style, defined as helicopter parenting, could be a risk factor for maladaptive behaviours in youth, including alcohol use and drug consumption. However, such at-risk behaviours have also been associated with low levels of parental involvement and warmth. Thus, the relationship between parental involvement and at-risk behaviours in adolescents is not clear. The purpose of the current study was to identify the relation between helicopter parenting and alcohol use in a sample of Italian youth.Design: The participants were 402 adolescents (233 female) between the ages of 14 and 19 years ( M age = 17.20, SD = 1.66). Hierarchical multiple regression analyses were conducted to examine linear, quadratic, and exponential models and to verify which model best described the correlation.Results: The results showed a quadratic correlation between mothers' helicopter parenting and alcohol use, whereby higher and lower levels of mothers' helicopter parenting were associated with adolescents' alcohol use.Conclusions: The empirical data are essential for improving our understanding of the implications and potential outcomes of helicopter parenting during adolescence.